PENGARUH BERBAGAI JENIS KAPUR DALAM APLIKASI PENGAPURAN UNTUK MEMPERBAIKI SIFAT KIMIA ULTISOL - Amsar Maulana; H Herviyanti; Teguh Budi Prasetyo (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2020)
Liming increases soil fertility through improved soil conditions in acidic soils (Ultisols). This study aimed to determine the effect of limes [CaO; Ca(OH)2; CaCO3 and CaMg(CO3)2 ] on the chemical properties of Ultisols of Limau Manis Padang. Treatments tested in this study application of four types of lime, i.e. A = CaO; B = Ca(OH)2; C = CaCO3; dan D = CaMg(CO3)2. on an Ultisol. A control treatment with no application of lime was also included in this study. After incubation of the soil-lime mixtures for two weeks, the results of the study showed that liming using dolomite [CaMg(CO3)2] was more effective in improving the chemical properties of Ultisols, compared to other types of lime [CaO; Ca(OH)2; CaCO3]. The effect of dolomite on 1*exchangeable Al (1 me Ca 100 g-1) improved chemical properties of an Ultisol from Limau Manis Padang such as pH H2O by 0.35 unit, available P by 1.03 ppm, exchangeable Al by 0.91 cmolc kg-1; exchangeable H by 0.92 cmolc kg-1; CEC by10.49 cmolc kg-1; exchangeable K by 0.03 cmolc kg-1; exchangeable Ca by 0.44 cmolc kg-1 and exchangeable Mg by 1.34 cmol ckg-1, compared to control.